T–S fuzzy controller design for stabilization of nonlinear networked control systems. (April 2016) - Marouf, Sepideh; Mahboobi Esfanjani, Reza; Akbari, Ahmad; Barforooshan, Mohsen
Abstract: This paper concerns with the problem of stabilization of nonlinear networked systems which are described by type-1 T–S fuzzy model. Based on Lyapunov–Krasovskii theorem, a novel procedure is derived to design a T–S fuzzy controller to asymptotically stabilize the nonlinear networked control system (NCS). The main novelty of the proposed method is to incorporate the grades of memberships of the plant model in the controller synthesis criterion which increases the maximum tolerable delay in the closed loop system. Two comparative examples are presented to verify the applicability and outperformance of the introduced scheme compared to some of existing approaches in the literature.